Impaired sequence generation: a preliminary comparison between high functioning autistic and neurotypical adults - Heleven, Elien; Bylemans, Tom; Ma, Qianying; Baeken, Chris; Baetens, Kris (Frontiers in Behavioral Neuroscience, 2022)
Earlier research demonstrated robust cerebellar involvement in sequencing, including high-level social information sequencing that requires mental state attributions, termed mentalizing. Earlier research also found cerebellar deficiencies in autism spectrum disorders (ASD) which are characterized by social difficulties. However, studies on high-level social sequencing functionality by persons with ASD are almost non-existent. In this study, we, therefore, perform a comparison between behavioral performances of high-functioning ASD and neurotypical participants on the Picture and Verbal Sequencing Tasks. In these tasks, participants are requested to put separate events (depicted in cartoon-like pictures or behavioral sentences, respectively) in their correct chronological order. To do so, some of these events require understanding of high-level social beliefs, of social routines (i.e., scripts), or nonsocial mechanical functionality. As expected, on the Picture Sequencing task, we observed longer response times for persons with ASD (in comparison with neurotypical controls) when ordering sequences requiring an understanding of social beliefs and social scripts, but not when ordering nonsocial mechanical events. This confirms our hypotheses that social sequence processing is impaired in ASD. The verbal version of this task did not reveal differences between groups. Our results are the first step toward new theoretical insights for social impairments of persons with ASD. They highlight the importance of taking into account sequence processing, and indirectly the cerebellum when investigating ASD difficulties.